2016
DOI: 10.1007/s12529-016-9549-8
|View full text |Cite
|
Sign up to set email alerts
|

The Cyberchondria Severity Scale (CSS): German Validation and Development of a Short Form

Abstract: The German version of the CSS possesses very good psychometric characteristics, which were preserved in a short version. The factorial structure was replicated. The correlations with health anxiety and depression for both scales underscore their validity and clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 34 publications
5
122
2
9
Order By: Relevance
“…The first meta-analysis included 10 studies (Baumgartner & Hartmann, 2011;Doherty-Torstrick, Walton, & Fallon, 2016;Fergus, 2013;Fergus & Dolan, 2014;Lagoe & Atkin, 2015;Lee & Hawkins, 2016;Muse, McManus, Leung, Meghreblian, & Williams, 2012;Singh & Brown, 2014;Singh & Brown, 2016;Tanis, Hartmann, & te Poel, 2016). The second meta-analysis also included 10 studies (Bajcar et al, 2018;Barke, Bleichhardt, Rief, & Doering, 2016;Fergus, 2014;Fergus, 2015;Fergus & Russell, 2016;Fergus & Spada, 2017;Mathes, Norr, Allan, Albanese, & Schmidt, 2018;Norr, Albanese, Oglesby, Allan, & Schmidt, 2015;Selvi et al, 2018). An overview of the included studies is shown in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first meta-analysis included 10 studies (Baumgartner & Hartmann, 2011;Doherty-Torstrick, Walton, & Fallon, 2016;Fergus, 2013;Fergus & Dolan, 2014;Lagoe & Atkin, 2015;Lee & Hawkins, 2016;Muse, McManus, Leung, Meghreblian, & Williams, 2012;Singh & Brown, 2014;Singh & Brown, 2016;Tanis, Hartmann, & te Poel, 2016). The second meta-analysis also included 10 studies (Bajcar et al, 2018;Barke, Bleichhardt, Rief, & Doering, 2016;Fergus, 2014;Fergus, 2015;Fergus & Russell, 2016;Fergus & Spada, 2017;Mathes, Norr, Allan, Albanese, & Schmidt, 2018;Norr, Albanese, Oglesby, Allan, & Schmidt, 2015;Selvi et al, 2018). An overview of the included studies is shown in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Consequently, the strength of associations reported in the present review rely on the validity and reliability of this measure, which has been criticized for taking a broad approach to cyberchondria by including items that may be irrelevant and non-specific (Starcevic & Berle, 2015). Additionally, the original five-factor structure for this instrument has been called into question because one subscale (i.e., mistrust of medical professionals) has been found to have poor model fit (e.g., Barke, Bleichhardt, Rief, & Doering, 2016;Fergus, 2014). Second, most of the studies relied upon self-report as a measure of online health information searching.…”
Section: Despite Finding An Association Between Health Anxiety and Onmentioning
confidence: 99%
“…Finally, in the German validation study, the internal consistency of the scale was found to be α= .93 and split-half reliability to be α= .95. The 'Mistrust of Medical Professional' subscale had relatively low internal reliability (α = .74) similar in the initial validation even if it was acceptable (Barke, Bleichhardt, Rief, & Doering, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…This instrument has been criticised for being too broad, encompassing items that are not necessarily relevant or specific for cyberchondria and giving cyberchondria almost a status of a disorder, with its subscales and dimensions resembling the diagnostic criteria [2]. The Cyberchondria Severity Scale also has some psychometric deficiencies in that its original five-factor structure could not be confirmed, with a suggestion that one of its subscales, mistrust of medical professionals, should be omitted [25,26,27]. All this calls for the development of a refined assessment tool for cyberchondria and longitudinal, prospective studies conducted in various populations, including clinical samples.…”
Section: Outlook For the Futurementioning
confidence: 99%